ANALISIS PENGARUH PENGETAHUAN DAN PEMAHAMAN PERPAJAKAN, PELAYANAN FISKUS, KESADARAN PERPAJAKAN, PENDAPATAN WAJIB PAJAK, DAN SISTEM ADMINISTRASI MODERN TERHADAP KEPATUHAN WAJIB PAJAK - Dinda Prostina Nukfikhasari, 14.05.62.0031; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2017)
This study aims to examine the influence of knowledge and understanding of taxation, fiscal services, tax awareness, taxpayer income, and modern tax administration system of taxpayer compliance. The population in this study is a four wheel taxpayer in Samsat II Semarang. Sampling was done by using convenience sampling method and the number of samples were 90 respondents. The primary data collection method use was survey method using questionnaire. Data obtained from the  questionnaire were analyzed using multiple linier regression model. The result showed that the variable knowledge and understanding of taxation have a significant negative effect on taxpayer compliance. While tax service variable, tax awareness, taxpayer income, and modern tax administration system have significant positive effect on taxpayer compliance.Keywords: Knowledge and Understanding of Taxation, Fiscal Service, Tax Awareness, Taxpayer Income, Modern Tax Administration System, and Taxpayer Compliance